A study on the correlation between function motivation and professional identity among nursing volunteers - Juan Xu; Wenjun Hao; Hui Yang; Xuanxuan Li (Wolters Kluwer Medknow Publications, 2021)
Objective: The objective of this study is to understand the status quo of function motivation and professional identity among nursing volunteers and explore the correlation between the two. Materials and Methods: A total of 3375 nursing volunteers from Nightingale Volunteer Service Group in Shanxi Province were investigated by using Occupational Identity Scale and Volunteer Functional Motivation Scale. Results: A total of 3375 questionnaires were issued and 3330 were recovered, among which 3324 were valid, with an effective recovery rate of 99.82% (3324/3330). The overall score of professional identity of nurses was 110.31 ± 18.71, and the score of each dimension was 32.17 ± 6.62 for professional cognitive evaluation dimension, 22.77 ± 3.74 for professional social support, 21.31 ± 4.09 for professional social skills, 22.78 ± 3.79 for professional frustration coping, and 11.32 ± 2.03 for professional self-reflection. The total score of function motivation was 157.12 ± 29.92. The above five dimensions of nurse's professional identity scale were positively correlated with the total score of function motivation of nursing volunteers (r = 0.044, 0.035, 0.034, 0.035, and 0.042, respectively, all P < 0.05). Conclusion: The functional motivation and professional identity of nursing volunteers in Shanxi Province are in the middle level in China. Therefore, it is necessary for the hospital to stimulate nursing staff's enthusiasm about participation by carrying out multi-channel and multi-form volunteer service projects, enhance their professional identity, and make them better give back nursing professional skills to the society.